EXPLORING HABIB TANVIR’S NARRATIVE TECHNIQUES: A STUDY OF HIS MAJOR PLAYS - Pushpa Mishra, Dr. Sunayana Mishra (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Habib Tanvir, a prominent figure in Indian theatre, revolutionized the landscape of Indian drama with his unique narrative technique. This abstract excavates an investigation of Tanvir’s narrative style, focusing on his significant plays and the critical commitments to the dramatic domain. Through a careful examination of his works, this study reveals the intricate folds of Tanvir’s narrative technique, revealing insight into its creative components and its significant effects on the people. Tanvir’s narrative approach is characterized by its amalgamation of folk traditions, indigenous forms, and contemporary themes, making a rich embroidery of social accounts. His plays often draw inspiration from folk tales, myths, and local legends, seamlessly weaving them into the fabric of modern storytelling. The mixing of customary and contemporary components enhances the story surface as well as fills in as a mechanism for social commentary and cultural critique. The use of indigenous languages and dialects, particularly Chhattisgarhi, which adds authenticity and depth to the portrayal of rural life and indigenous cultures in his plays. Through the employment of these linguistic nuances, Tanvir captures the essence of rural India, portraying its complexities, struggles, and aspirations with sensitivity and empathy. Tanvir’s narrative style is characterized by its dynamic depiction of characters and communities. His plays frequently highlight an assorted cast, each addressing various features of society. Through distinctive portrayals and convincing discourse, Tanvir gives voice to the marginalized and oppressed, challenging societal norms and advocating for social justice. The innovative use of music, dance, and improvisation enhances the immersive experience of his plays, engaging the audience on multiple sensory levels. His incorporation of folk music and traditional forms of performance not only enriches the cultural tapestry of his plays but also serves as a bridge between past and present, tradition and modernity. Through a definite investigation of Tanvir’s significant plays, including Charandas Chor, Agra Bazar, and Bahadur Kalarin, this study tries to disentangle the intricacies of his narrative technique and its profound impact on Indian theatre. By examining the thematic concerns, structural innovations, and performative aspects of his works, this study aims to illuminate the enduring legacy of Habib Tanvir as a pioneering playwright and visionary storyteller.